Dissecting the thermodynamic contributions of the charged residues in the membrane anchoring of Bcl-xl C-terminal domain. (January 2019) - Maity, Atanu; Sinha, Souvik; Ghosh Dastidar, Shubhra
Highlights: C-terminal double mutation (R232A and K233A) impedes Bcl-xl C-tail insertion. Only one C-terminal polar residue (R232 or K233) is able to drive the insertion. C-terminal double mutant forces the peptide to disrupt membrane rigidity. N-terminal double mutant (N211A and R212A) only affects thermodynamic stability of membrane inserted state. Abstract: The C-terminal helix of the Bcl-xl is known to initiate the membrane insertion of the protein by anchoring into the mitochondrial outer membrane. The C-terminal charged residues of that helix, R232 and K233, are reported to have an important structural role in the process of that insertion. The present work provides a quantitative understanding of the thermodynamic contribution of these residues on the membrane insertion energy-profile, calculated from the Adaptive Biasing Force based MD simulations of 2.67 μs altogether. Interestingly, the effect of the single neutralizing mutations at the C-terminus, i.e. K233A or R232A, is easily tolerated by the peptide without impacting the nature of insertion energy-profile, indicating the efficiency of one positively charged residue to drive the insertion. Whereas a double mutant, i.e. R232A and K233A, makes a significant impact on the energy-profile by destabilizing the membrane-associated states, as well as the membrane-embedded states. The finding provides molecular-level mechanistic insight. The water-mediated interaction formed by the peptide polar side chains within the bilayer core is found to modulate the membrane response during peptide insertion and that subsequently regulates the insertion mechanism. Mutation of the C-terminal residues eventually alters such a cascade of interactions that results in an insertion through energetically more expensive pathway. Since any one of the positively charged residues at the terminal is critical to ensure the membrane insertion, it appears that the natural selection of 'two' instead of 'one' charged residue is redundant in the context of membrane anchoring but may be important for other biochemical events.